Zebrafish models for glucocorticoid-induced osteoporosis - Lin, Wen-Ying; Dharini, Kameshwara; Peng, Cheng-Huan; Lin, Chung-Yen; Yeh, Kuang-Ting; Lee, Wen-Chih; Lin, Ming-Der (Ci ji yi xue za zhi, 2022)
Glucocorticoid-induced osteoporosis (GIOP) is the most common form of secondary osteoporosis due to excessive or long-term glucocorticoid administration, disturbing the homeostasis between bone formation and bone resorption. The bone biology of zebrafish shares a high degree of similarities with mammals. In terms of molecular level, genes and signaling pathways related to skeletogenesis are also highly correlated between zebrafish and humans. Therefore, zebrafish have been utilized to develop multiple GIOP models. Taking advantage of the transparency of zebrafish larvae, their skeletal development and bone mineralization can be readily visualized through in vivo staining without invasive experimental handlings. Moreover, the feasibility of using scales or fin rays to study bone remodeling makes adult zebrafish an ideal model for GIOP research. Here, we reviewed current zebrafish models for GIOP research, focused on the tools and methods established for examining bone homeostasis. As an in vivo, convenient, and robust model, zebrafish have an advantage in performing high-throughput drug screening and could be used to investigate the action mechanisms of therapeutic drugs.